Corpus-based approaches to grammar, media and health discourses systemic functional and other perspectives - Yang, Bingjun 1971-; Li, Wen (The M.A.K. Halliday Library functional linguistics series, 2020)
This edited volume gathers corpus-based studies on topics including English grammar and discourses on media and health, mainly from a systemic functional linguistics (SFL) perspective, in order to reveal the potential of SFL, which has been emphasized by Halliday. Various other perspectives, such as philosophy, statistics, genre studies, etc. are also included to promote SFLs potential interaction with other theories. Though they employ a diverse range of theoretical perspectives, all the chapters focus on exploring language in use with the corpus method. The studies collected here are all original, unpublished research articles that address significant questions, deepen readers understanding of SFL, and promote its potential interaction with other theories. In addition, they demonstrate the great potential that SFL holds for solving language-related questions in a variety of discourses